Tribological Performance of Chemically Modified D. stocksii Bamboo Fibers in Composite Applications - Jiyas N; Indu Sasidharan; Bindu Kumar K; P. Senthamaraikannan; R. Kumar (Journal of Natural Fibers, 2025)
Natural fibers provide an eco-friendly alternative to synthetic reinforcements in composites, with Dendrocalamus stocksii (D. stocksii) fibers emerging as a superior option. However, their high hydrophilicity and reduced crystallinity limit their potential in advanced engineering applications. This study examines the effects of mercerization, benzoylation, and potassium permanganate treatments on the structural, physical, thermal, and mechanical properties of D. stocksii fibers. Among these, benzoyl chloride treatment significantly enhanced hydrophobicity, crystallinity, interfacial bonding, and overall performance. The treated fiber (BDSCF) exhibited a 15.4% increase in cellulose content (84.1%), 50% higher density (1620 kg/m3), 76% greater tensile strength (738.74 MPa), and improved thermal stability (Tmax: 366°C). The resulting friction composite (BDSCC) demonstrated 46% higher compressive strength (34.86 MPa), 87 HRS hardness, 85.1% lower void content, and reduced moisture and water absorption (21% and 50.6%, respectively). Additionally, BDSCC maintained exceptional frictional stability (95–96%) with a coefficient of friction (0.35–0.51) well within industry standards, alongside a significantly lower specific wear rate. Morphological analysis by scanning electron microscopy further validated superior bonding, reduced porosity, and enhanced wear resistance. These advancements position BDSCF and BDSCC as optimal candidates for high-performance, moisture-resistant, and thermally stable composite applications, particularly in tribological environments like brake pads and clutch pads.